The Production of Blue Cheese with the Addition of Nonpathogenic Strain of Klebsiella pneumoniae and Fortification of Folic Acid and Iron - WIDYA AGUSTINAH; FLORENTINUS GREGORIUS WINARNO (Indonesian Society for microbiology, 2010)
Blue cheese is a semi-soft ripened cheese that involves the growth of Penicillium roqueforti in the ripening process. Cheese has a longer shelf life compared to raw milk and the production of cheese will give added value to the finished product, which, therefore, can benefit local dairy farmers in Indonesia. The objective of this study was to produce a new variant of blue cheese which was made from a mixture of fresh cow's milk (Frisian Holstein cow) and skimmed milk powder and which had a high vitamin B12, folic acid, and iron content. Blue cheeses for this study were made by milk fermentation with the addition of a nonpathogenic strain of Klebsiella pneumoniae in the cheese preparation and fortification of folic acid and iron. This study showed that blue cheeses had been successfully made from a mixture of fresh cow's milk and skimmed milk at a ratio of 1:1 and acceptable by 42 untrained panelists. Compared to the commercial blue cheese, the addition of K. pneumoniae (0.8% v/v) and fortification (0.08 g L-1 of premix) had positive effects in increasing the amount of vitamin B12, folic acid, and iron up to 2.7, 13.64, and 102.86 ppm on dry-weight basis, respectively. However, blue cheese made without K. pneumoniae was the most preferred and had the highest scores for texture, taste and aroma.